Cardiovascular Diseases: An Overview for Treatment Strategies and Diagnostic Tools - Alnamy, Ahmad Musaddif M; Alqahtani , Muteb Aied; Al Rabie , Amer Khadeer Awedah; Alayyafi, Zainah Ali Abdullah; Alshehri, Budur Ali Ahmed; Asiri, Abdulqader Mohammed Joud Allah; Albarqi, Amer Musa Mnhmmad; Barqi, Hassan Ali Hassan; Al-Ameedi, Abdullah Bajad; Alfaris, Izzuldeen Ali; Alshehri, Shaker Abdullah; Alribi, Mohammed Hassan Ali (Journal of Ecohumanism, 2024)
Background: Cardiovascular disease (CVD) remains a leading cause of global morbidity and mortality, encompassing conditions such as coronary artery disease (CAD), cerebrovascular disease, peripheral artery disease (PAD), and aortic atherosclerosis. Atherosclerosis, driven by risk factors like dyslipidemia, hypertension, and lifestyle habits, underlies many CVDs. Despite advancements in diagnosis and treatment, the prevalence of CVD continues to rise, necessitating effective prevention and management strategies. Aim: This article provides an overview of CVD, focusing on its pathophysiology, epidemiology, diagnostic tools, and treatment strategies. It emphasizes the importance of risk factor modification, early detection, and interprofessional collaboration of pharmacists, clinical pathologists, epidemiology workers, and medical records workers in improving patient outcomes. Methods: The review synthesizes evidence from landmark studies, such as the INTERHEART and Framingham Heart studies, and current guidelines from organizations like the American Heart Association (AHA). It explores the role of diagnostic tools, including electrocardiograms, cardiac enzymes, and advanced imaging techniques, alongside emerging methods like coronary artery calcium (CAC) scoring. Results: CVD is influenced by both modifiable (e.g., smoking, physical inactivity) and non-modifiable (e.g., age, family history) risk factors. Early detection and management of atherosclerosis are critical for prevention. Interprofessional care models have demonstrated improved outcomes in heart failure and CAD, reducing mortality and hospital readmissions. Emerging therapies, such as PCSK9 inhibitors and SGLT2 inhibitors, show promise in managing CVD. Conclusion: Addressing CVD requires a multifaceted approach, including lifestyle modifications, pharmacological interventions, and interprofessional collaboration. Public health initiatives and patient education are essential for reducing the global burden of CVD.